Spectral Study of 1, 4-bis(3-(2-pyridyl)pyrazol-1ylmethyl)benzene (PPB): UV-VIS Absorption Spectra Investigation in Single and Binary Solvents and Spectrophotometric Determination of the Dissociation Constant (pKb). Issue 1 (2017) - Elsherif, Khaled Muftah
No abstract available